A Novel Protein Encoded by Exosomal CircATG4B Induces Oxaliplatin Resistance in Colorectal Cancer by Promoting Autophagy. Issue 35 (26th October 2022) - Pan, Zihao; Zheng, Jun; Zhang, Jiebin; Lin, Jiatong; Lai, Jianguo; Lyu, Zejian; Feng, Huolun; Wang, Junjiang; Wu, Deqing; Li, Yong
Abstract: Oxaliplatin is commonly used in chemotherapeutic regimens for colorectal cancer (CRC) after surgical resection. However, acquired chemoresistance seriously affects the curative effect in CRC patients, and the mechanism is still unclear. Here, a circular RNA, circATG4B is identified, which plays an important role in oxaliplatin resistance in CRC. circATG4B expression is found to be increased in exosomes secreted by oxaliplatin‐resistant CRC cells. In addition, the results suggest that circATG4B induces oxaliplatin resistance by promoting autophagy. Further in vivo and in vitro studies indicate that the effect of circATG4B is attributed to its potential to encode a novel protein, circATG4B‐222aa. Next, circATG4B‐222aa is found to function as a decoy to competitively interact with TMED10 and prevent TMED10 from binding to ATG4B, which leads to increased autophagy followed by induction of chemoresistance. Therefore, this study reveals that exosomal circATG4B participates in the decreased chemosensitivity of CRC cells, providing a new rationale for a potential therapeutic target for oxaliplatin resistance in CRC. Abstract : In recent years, significant attention has focused on circRNA translation to determine its clinical significance. The present study describes the physiological role of a novel protein encoded by circATG4B. These findings may shed light on the protein‐coding potential of circRNAs during drug resistance progression and provide a precise intervention target for the treatment of chemoresistant colorectal cancer.